BETACYANIN ASSAYS OF FRUIT BEET (Beta vulgaris L.) WITH SOLVENT ETHANOL AS A BIOLOGY LEARNING OBJECT MATERIAL - Sari, Nelvita Mei Indah (University of Muhammadiyah Malang, 2016)
Beet (Beta vulgaris L.) or often also known as beet root is a plant form that is similiar roots and tubers family Amaranthaceae. Physical characteristics of fruit bits are round like a potato tuber with a dark red-purple color and its fruit will be cut when the line visible in white with pink. In bits are main components of the pigment betasianin. Betasianin are dyes that cangive red color, can be found in fruits, flowers and vegetative tissues. Betasianin canbe used as natural dyes in food. The purpose of this study was to determine the anthocyanin content test on beet (Beta vulgaris L). This type of research is True Experimental Research. The study design used is The Posttest-Only Control Group Design. The design ofthis study using a completely randomized design (CRD). The solvent comprises ethanol percentage of 80%, 50%, 20% and 0% for the control treatment. The data in this study of value betasianin levels. Analysis of the data in this study using analysis of variance of the factors where the results of this study indicate the best treatment of data betasianin assay lies in ethanol with a percentage of 50% with a value of 0.089. This can have an influence because the volume ratio of water and ethanolis the same.